Ionizing radiation resilience: how metabolically active lichens endure exposure to the simulated Mars atmosphere - Kaja Skubała; Karolina Chowaniec; Mirosław Kowaliński; Tomasz Mrozek; Jarosław Bąkała; Ewa Latkowska; Beata Myśliwa-Kurdziel (IMA Fungus)
To deepen our understanding of lichen adaptation and their potential to colonize extraterrestrial environments, we aimed to identify physiological/biochemical responses of selected lichen species in a metabolically active state to simulated Mars-like conditions in the dark including exposure to X-rays. Our study is the first to demonstrate that the metabolism of the fungal partner in lichen symbiosis was active while being in a Mars-like environment. Diploschistes muscorum was able to activate defense mechanisms effectively. In contrast, increased oxidative stress and associated damage were not effectively balanced in C. aculeata, which does not support the melanin’s radioprotective function in this species. The heavy crystalline deposit on D. muscorum thallus might offer protection enhancing lichen resistance to extreme conditions. We concluded that metabolically active D. muscorum can withstand the X-ray dose expected on the Mars surface over one year of strong solar activity. Consequently, X-rays associated with solar flares and SEPs reaching Mars should not affect the potential habitability of lichens on this planet.